2010
DOI: 10.1111/j.1365-2966.2010.17688.x
|View full text |Cite
|
Sign up to set email alerts
|

The dance of heating and cooling in galaxy clusters: three-dimensional simulations of self-regulated active galactic nuclei outflows

Abstract: It is now widely accepted that heating processes play a fundamental role in galaxy clusters, struggling in an intricate but fascinating 'dance' with its antagonist, radiative cooling. Lastgeneration observations, especially X-ray, are giving us tiny hints about the notes of this endless ballet. Cavities, shocks, turbulence and wide absorption lines indicate that the central active nucleus is injecting a huge amount of energy in the intracluster medium. However, which is the real dominant engine of self-regulat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
119
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(137 citation statements)
references
References 109 publications
12
119
0
Order By: Relevance
“…The metal-rich columns of gas extending tens to hundreds of kiloparsecs in elevation are thought to trace hot flows lifted outward by radio bubbles (Simionescu et al 2008;Kirkpatrick et al 2009Kirkpatrick et al , 2011Werner et al 2010;Werner et al (2011)). This phenomenon is also seen in hydrodynamic simulations where metal-enriched gas in the central galaxy is propelled outward in the updraft of rising bubbles (Pope et al 2010;Gaspari et al 2011). Estimated flow rates of several tens of solar masses per year would be sufficient to account for the observed molecular gas masses.…”
Section: Does Molecular Gas Condense From Hot Outflows?mentioning
confidence: 60%
“…The metal-rich columns of gas extending tens to hundreds of kiloparsecs in elevation are thought to trace hot flows lifted outward by radio bubbles (Simionescu et al 2008;Kirkpatrick et al 2009Kirkpatrick et al , 2011Werner et al 2010;Werner et al (2011)). This phenomenon is also seen in hydrodynamic simulations where metal-enriched gas in the central galaxy is propelled outward in the updraft of rising bubbles (Pope et al 2010;Gaspari et al 2011). Estimated flow rates of several tens of solar masses per year would be sufficient to account for the observed molecular gas masses.…”
Section: Does Molecular Gas Condense From Hot Outflows?mentioning
confidence: 60%
“…The total amount of cold gas in the last stage is larger in our simulations likely because our model cluster is much more massive than that in Cattaneo & Teyssier (2007). Gaspari et al (2011) studied the momentum-driven AGN feedback with mass-loaded outflows, and also found that the results are not very sensitive to the efficiency in their coldregulated feedback model. Vernaleo & Reynolds (2006) finds that simple hydro jets cannot prevent a cooling catastrophe because most of the energy channels out of the cool core.…”
Section: Comparison With Previous Simulationsmentioning
confidence: 86%
“…Previous simulations on AGN feedback in cool-core clusters have been focusing on how AGN deposits its energy and whether cooling can be balanced (e.g., Soker et al 2001;Vernaleo & Reynolds 2006;Gaspari et al 2011). It has been found that momentum-driven AGN feedback can indeed suppress cooling over a few Gyr timescale (e.g., Cattaneo & Teyssier 2007;Gaspari et al 2011), and Gaspari et al (2012) has also seen the formation of multiphase gas, suggesting that momentumdriven AGN feedback is a very successful model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accretion rate calculations can vary from the simple Bondi rate (Bondi 1952) to estimates of viscous angular momentum transport (Debuhr et al 2010) to fully stochastic models (Pope 2007). If the resolution and computing resources permit it, large-scale jets can be placed on the simulation grid with many modifications, including simple fluxes at cell boundaries (Gaspari et al 2011), limited-lifetime jets (Morsony et al 2010), extended jets (Cattaneo & Teyssier 2007), wide-angle jets (Sternberg, Pizzolato & Soker 2007) and precessing jets (Sternberg & Soker 2008;Falceta-Gonçalves et al 2010a). Since jets eventually inflate bubbles, it is easier computationally to simply place already formed bubbles (e.g.…”
Section: Introductionmentioning
confidence: 99%